Karâmah Maryam 'Inda Jamâl ad-Dîn al-Qâshimy fi Tafsîrih Maḥâsin at-Ta'wîl - Ahmad Suharto; Khansa Azizah (Universitas Darussalam Gontor, 2018)
Maryam is one of women whom Allah tells in the Qur'an, who had place with Allah enshrined into one of the suras in the Qur'an. There are many signs of Maryam's magnificence that appears from her birth to adulthood. The magnificence illustrated by the protection of God as a holy woman, sudden sustenance, and the birth of a baby without a man. Jamaluddin al-Qasimi in his Book of Maḥâsin at-Ta'wîl with the 'aqly ijtihâdy approach which adheres to the history of mutawâtir and wich is is free from the history of israiliyyah, place this phenomenon as karomah. This paper examines the karomah to Maryam in the Qur'an with a thematic approach in Jamaluddin al-Qasimi perspective